The 2008 general elections: implications for ethnic relations in Malaysia - Jawan, Jayum; Yusoff, Mohammad Agus (2008)
This paper aim to discussion the impact of the results of the 2008 general elections upon inter ethnic relations in Malaysia. Many assumptions have been previously provided the basis for understanding and explaining Malaysia's harmonious inter ethnic relations that has sustained political stability, economic progress and social harmony for the lasst fifty years. But the results of the 2008 general elections challenged all that. What's more with many political developments that appear to plunge the whole governing system into a crisis of confidence. In line with the above scenario, specific issues and challenges that this paper addresses with regard to the landmark general elections, are namely: how will inter ethnic relations change?; Is democracy and the emergence of a two party system sustainble? Will Malaysia be able to weather this sudden change place upon its political system?